2012
DOI: 10.1016/j.cbpa.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Retention of different-sized particles and derived gut fill estimate in tammar wallabies (Macropus eugenii): Physiological and methodological considerations

Abstract: Clauss, M. (2012). Retention of different-sized particles and derived gut fill estimate in tammar wallabies (Macropus eugenii): physiological and methodological considerations. Comparative Biochemistry and Physiology Part A: Molecular and Integrative Physiology, 161 (2), 243-249. Retention of different-sized particles and derived gut fill estimate in tammar wallabies (Macropus eugenii): physiological and methodological considerations AbstractThe capacity of the digestive tract is an important parameter in unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The results for ponies are in line with those for other large, nonruminant foregut fermenters including macropods, peccaries, hippos and colobine monkeys, in which no selective retention of a certain particle size fraction was observed (Matsuda et al, 2015;Munn, Tomlinson, Savage, & Clauss, 2012;Schwarm, Ortmann, Wolf, Streich, & Clauss, 2009;Schwarm et al, 2008). Anyhow, a selective retention of large particles in a non-ruminant herbivore appears unlikely.…”
Section: Discussionsupporting
confidence: 82%
“…The results for ponies are in line with those for other large, nonruminant foregut fermenters including macropods, peccaries, hippos and colobine monkeys, in which no selective retention of a certain particle size fraction was observed (Matsuda et al, 2015;Munn, Tomlinson, Savage, & Clauss, 2012;Schwarm, Ortmann, Wolf, Streich, & Clauss, 2009;Schwarm et al, 2008). Anyhow, a selective retention of large particles in a non-ruminant herbivore appears unlikely.…”
Section: Discussionsupporting
confidence: 82%
“…At any particular distance from the sacculated forestomach in the tubiform organ (or haustral pouch), biofilm consortia can be expected to be at the same stage of development, growth, maturation and detachment. This expectation is reinforced by the fact that differently sized particles travel at the same rate during digesta passage through the forestomach of macropods (Munn et al 2012).…”
Section: Factors Affecting the Nature And Microbial Composition Of Bimentioning
confidence: 99%
“…Holleman and White (1989) and Munn et al (2012) showed that assuming 175 a linear course of digestion across MRT yields better results when validated against empirical 176 measures in slaughtered animals, albeit using small sample sizes. Because assuming a linear 177 course of digestion across MRT means that dDMC is assumed to be present in the GIT during 178 half of MRT, it follows that 179 dDMC [kg] = DMI [kg/h] * aD DM * (MRT particle GIT [h] / 2) (6).…”
Section: Introduction 59mentioning
confidence: 99%
“…If in addition to measures of food 210 intake and digesta retention, the apparent digestibility of dry matter is also measured in the 211 same feeding trial, the derivation of indigestible and complete gut fill (as DMC) as indicated 212 in the equations above is possible. Although this has been done repeatedly in individual 213 studies to compare selected species, or make intraspecific or inter-clade comparisons (Baker 214 and Hobbs, 1987;Gross et al, 1996;Behrend et al, 2004;Munn 215 and Barboza, 2008;Clauss et al, 2010b;Franz et al, 2011b;Sawada 216 et al, 2011;Fritz et al, 2012;Munn et al, 2012), a large-scale comparison of mammalian 217 herbivore gut fill has not been performed so far. Therefore, it is the aim of this study to 218 explore the scaling of food intake, digesta retention, apparent digestibility and the calculated 219 gut fill in mammalian herbivores, using available literature data.…”
mentioning
confidence: 99%